COHESIVE DEVICES USED IN THE HEADLINE NEWS OF THE JAKARTA POST - Vany Tarsidasari Jambak; Busmin Gurning (State University of Medan, 2014)
ABSTRACT The study deals with the types of cohesive devices used in Headline News of The Jakarta Post. The objectives of study are to identify and to derive the types of cohesive devices dominantly used in headline news of the Jakarta Post. The data are taken from headline column of The Jakarta Post from online edition. There are seven articles which are analyzed in this study. This research is conducted by using descriptive method. The findings show that there are 162 references, 4 substitutions, 34 Ellipsis, 349 conjunctions, and 36 lexical cohesion occur in this study. The most dominant type of cohesive devices is conjunction because the writer would like to connect ideas within the text to make its readers easy to understand. Then the writer would like to make their news more informative. Keyword : cohesion, cohesive device, The Jakarta Post.